2008
DOI: 10.1517/17460441.3.11.1309
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic considerations for Mdm2: not just a one trick pony

Abstract: Background-The mdm2 proto-oncogene is elevated in numerous late stage cancers. The Mdm2 protein manifests its oncogenic properties in part through inactivation of the tumor suppressor protein p53. Recent efforts in anti-cancer drug design have focused on the identification of small molecules that disrupt the Mdm2-p53 interaction, in hopes of re-engaging the p53 pathway.Objective-In addition to binding p53, Mdm2 complexes with numerous proteins involved in DNA repair, translation, metabolic activities, tumor gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…Therefore, a fine-tuning mechanism between PTEN, p53, p73, and Mdm2 is in place in human cells to mediate cellular apoptosis in response to DNA damage. To this end, Mdm2 represents a viable target for drug design and chemotherapeutic intervention (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a fine-tuning mechanism between PTEN, p53, p73, and Mdm2 is in place in human cells to mediate cellular apoptosis in response to DNA damage. To this end, Mdm2 represents a viable target for drug design and chemotherapeutic intervention (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…2,8,9 The restoration of the impaired function of a single gene, p53, by directly disrupting the MDM2-p53/MDMX-p53 interactions, offers an attractive new avenue for anticancer therapy across a broad spectrum of cancers. [10][11][12][13][14][15][16][17][18][19][20] Cancer cells have been shown to be extremely sensitive to restoration of p53 function, verifying the expectation of highly effective therapies from this approach [21][22][23][24] and thus an intensive anticancer drug discovery effort is ongoing to develop antagonists of this interaction. While many MDM2 antagonists have been described in patent and scientific literature, no small molecule is known to tightly bind to MDMX.…”
Section: Introductionmentioning
confidence: 94%
“…[1][2][3][4][5][6][7][8][9] The rescue of the impaired p53 function by disrupting the Mdm2-p53 interaction offers new strategies for anticancer therapeutics. 2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Mdm2 promotes ubiquitination of p53 followed by degradation in proteasome. [1][2][3][4][5][6][7][8][9]23 Although Mdm2 remains the only known essential regulator of p53 stability, recently its homolog, Mdmx, has also emerged as an important player in the regulation of p53 activity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9]23 Although Mdm2 remains the only known essential regulator of p53 stability, recently its homolog, Mdmx, has also emerged as an important player in the regulation of p53 activity. [1][2][3][4][5]7,15,22,23 It was shown that the high-affinity Mdm2 inhibitors developed so far, e.g., Nutlins [11][12][13][14][15][16][17][18][19][20][21][22][23][24] or Mi219 (reviewed in refs. 11, 14, 15 and 25) are only weakly binding to Mdmx (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%